2019
DOI: 10.2147/dmso.s194591
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of abnormal glucose homeostasis in Chinese patients with non-transfusion-dependent thalassemia</p>

Abstract: Purpose: To determine the prevalence and underlying pathology of abnormal glucose homeostasis in Chinese patients with non-transfusion-dependent thalassemia (NTDT). Patients and methods: In this study, we enrolled 211 patients aged 4–63 years with NTDT, including 79 β thalassemia intermedia patients, 114 Hb H disease patients and 18 Hb E/β thalassemia patients. All had oral glucose tolerance test, serum ferritin (SF), homeostasis model assessment (HOMA) and liver iron concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Increase in hydroxyl free radicals production by the Fenton reaction and iron overload are mentioned as the causes of IMA formation in patients with thalassemia [13]. Increase in FBS and higher rate of insulin resistance was observed in our patients with β-TM, which are in agreement with the results reported by several previous studies [9,25]. As expected and in agreement with many previous studies [26], evaluation of liver function test in our patients showed abnormalities in all aspects of normal liver function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increase in hydroxyl free radicals production by the Fenton reaction and iron overload are mentioned as the causes of IMA formation in patients with thalassemia [13]. Increase in FBS and higher rate of insulin resistance was observed in our patients with β-TM, which are in agreement with the results reported by several previous studies [9,25]. As expected and in agreement with many previous studies [26], evaluation of liver function test in our patients showed abnormalities in all aspects of normal liver function.…”
Section: Discussionsupporting
confidence: 93%
“…In order to better predict CHD risk, several indices of dyslipidemia including LDL: HDL ratio ( atherogenic index; AI), log TG: HDL ratio (atherogenic index of plasma; AIP), TC: HDL ratio (coronary risk index ; CRI) are used to describe the significance of dyslipidemia in increasing risk of CHD in patients with β-TM [8]. Hyperglycemia, glucose intolerance, decreased beta cell activity and insulin insensitivity were reported in patients with β-TM [9]. OS due to decrease in antioxidant defense system and increase iron-induced ROS production as well as the benefits of antioxidant administration to overcome these disorders were implicated in patients with β-TM [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is noticeable that the proportion of pregnancy-induced diabetes was as high as 16.58% and 17.86% among pregnant α- and β-thalassemia carriers, respectively, which was largely higher than what was reported in thalassemia major patients (6.54–9.0%) [30,31] . Another study focused on Chinese populations reported that the prevalence of diabetes was 1.90% (4/211) among patients with non-transfusion-dependent thalassemia [32] . Attention should be paid to pregnancy-induced diabetes in thalassemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…[30,31] Another study focused on Chinese populations reported that the prevalence of diabetes was 1.90% (4/211) among patients with non-transfusion-dependent thalassemia. [32] Attention should be paid to pregnancy-induced diabetes in thalassemia patients. It should also be noted that a-thalassemia carriers might have worse pregnancy outcomes compared with b-thalassemia, especially for pregnancy-induced hypertension and eclampsia/ preeclampsia.…”
Section: Subtypesmentioning
confidence: 99%
“…Impaired glucose tolerance in symptomatic diabetes mellitus was substantiated for thalassemic patients. [ 16 ] An excess of deformed globin chains in thalassemic erythrocytes are deposited on the erythrocyte membrane, leading to membrane protein aggregation and binding to autoantibodies and complement, and this in turn promotes the rapid clearance of erythrocytes in the circulation. [ 17 ] Abnormalities of the innate immune system associated with thalassemia were reported including reduced absorption and phagocytic ability of polymorphonuclear neutrophils, and altered intracellular metabolic processes.…”
Section: Discussionmentioning
confidence: 99%